#TITLE_ALTERNATIVE# - FRANKLY SAMUEL PARDEDE (NIM : 10213022), KEVIN
One of the problems in physics is called the gauge hierarchy problem, which seeks an answer of the apparent discrepancy between two fundamental mass constants: electroweak and Planck mass. In this thesis, two specific brane-world are discussed: ADD and Randall-Sundrum model, which initial motivation is to solve the gauge hierarchy problem. A more general approach, which is the covariant formulation of brane-world is also discussed. Subsequently, the application of the brane-world to the cosmology is provided. The effect of the correction terms provided by the modified Friedmann equations are studied, and thus compared to the conventional model in determining the evolution of the universe. Numerical computational method is also performed to obtained the parameters of the modified Friedmann equation. It is found that the brane tension is not large enough to support a nucleosynthesis process which correctly reproduce the abundance of present light elements. Also, we found that the parameter related to the dark-radiation is positive, and thus indicating a possibility of evolution without singularity.